Stabilization of Black Cotton Soil by Fly Ash and Lime (Case of Debra Tsige Area) - Endalkachew, Belay (ASTU, 2023)
Black cotton soils are characterized by large volume change with changes in moisture condition. These characteristics of soils resulted in the failure of building structures in Debra Tsige area. The engineering properties of such soils can be improved through stabilization. Therefore the aim of this study is to investigate the stabilization of black cotton soil with lime and fly ash to improve its engineering properties. And it is making for stable soil of this area. In this study black cotton soil is stabilized by addition of optimum percent 6% of hydrated lime mixed with 5%, 10%, 15% and 20% of fly ash and got the significant results on engineering properties like Liquid limit, Plastic limit, Free swell index, standard compaction, consolidation, scanning electron microscope and unconfined compression strength values. The liquid limit, plastic limit and maximum dry density of the black cotton soil decreased and the optimum moisture content and unconfined compression strength values are increased when increase in percentage of fly ash contents from 5%-20% with optimum percent 6% of hydrated lime. It is concluded that treating black cotton soil with fly ash and lime enhances its strength. It also offers another way to dispose of fly ash.
Keywords: Black Cotton Soil, Stabilization, Engineering Properties, Fly ash, hydrated lime